Regulating Closed Pore Structure of Coal-Based Hard Carbon Anode by Preoxidation for High-Rate Performance Sodium-Ion Batteries - Hou, Shengping (Langmuir : the ACS journal of surfaces and colloids, 2025)
Coal-derived hard carbons (CHCs) have considerable potential as sodium storage materials because of their abundant resources and structural diversity. Nevertheless, the smaller layer spacing and ordered carbon microstructure of CHCs bring about low charge/discharge rates and poor cycle life of sodium-ion batteries (SIBs), rendering it challenging to support large-scale energy storage applications. Herein, the preoxidation strategy is employed to achieve multiscale structure optimization of CHCs and improve its sodium storage capacity. The oxygen content in preoxidized coal reached 15.2%, contributing to increasing the cross-linked structure of the coal materials. Particularly, insertion of Na+ is facilitated by large layer spacing of 0.394 nm, as well as the closed pores (0.162 cm3 g-1) improving the diffusion of Na+. Consequently, the rate performance of the as-optimized anode (OCHC3) is superior to that of directly carbonized. Specifically, OCHC3 exhibits a commendable rate performance (201 mAh g-1) and achieves outstanding cycling stability (96.2%) over 500 cycles. Furthermore, galvanostatic intermittent titration reveals the "adsorption-insertion-filling" of OCHC3. This study enlightens the rational design of high-performance HC anodes for SIBs and beyond